The Effect of the Ratio of Gamma Aminobutyric Acid-Producing Saccharomyces cerevisiae DL6–20 and Kluyveromyces marxianus B13–5 Addition on Cheese Quality - Li, Shan; Zhang, Yan; Li, Xu; Yin, Pingping; Wang, Tengbin; Li, Yandie; Zhang, Kaili; Sheng, Huayang; Lu, Shiling; Ji, Hua; Fan, Zhexin; Li, Baokun (Frontiers in Microbiology, 2022)
Kazakh cheese is a traditional dairy product in Xinjiang, China. The function and potential probiotic characteristics of Saccharomyces cerevisiae DL6-20 and Kluyveromyces marxianus B13-5 in Kazakh cheese and its contribution to cheese fermentation was studied. In this study, the effect of the addition ratio of GABA-producing Saccharomyces cerevisiae DL6-20 and Kluyveromyces marxianus B13-5 on cheese quality was investigated. Cheeses were prepared by fermentations with a total of six treatments: comercial culture alone as control (CS), a combination with one yeast, either; K. marxianus B13-5 (CSM); S. cerevisiae DL6-20 (CSS); and three different proportions of this two yeasts (CSM:CSS 1:1, 1:2, 2:1). We measured the gamma aminobutyric acid (GABA) content of cheese, as well as basic physical and chemical indicators, microbial content, free amino acid (FAA) content, texture, and flavor compound content. The total FAA content of mixed bacteria fermentation was higher than that of the single bacteria alone. The GABA content CSM:CSS 1:2 GABA content was 0.114g/100g, CSM:CSS 2:1 GABA content was 0.12g/100g, CSM:CSS1:1 content of GABA produced in the late ripening period of cheese was the highest, reaching 0.189 g/100g and the number of LAB and yeasts in CSM:CSS 1:1 was higher than that of other cheeses. The mixed-strain fermentation generally produced cheeses with a higher protein content than that of the single-strain fermentation in the late stage of the maturation process, especially the protein content of CSM:CSS 1:1 during the ripening period, when the protein content was highest at day 50. CSM:CSS 1:1 had a low moisture content, making it easy to store. With the exception of water and protein content, there is no significant difference in other physical and chemical indicators. CSM:CSS 1:1 contributed to the formation of cheese texture. In addition, multivariate statistical analysis indicated that mixed-strain fermentation was beneficial to the production of cheese aroma, with the aroma production performance of CSM:CSS 1:2 and CSM:CSS 2:1 found to be better than that of CSM: CSS 1:1.